Book Review: A Handbook for Women’s clothing, Northern Europe, 1360-1415 by Ahlqvist and Neijman - Catharina Oksen (EXARC Journal)
The book presents itself as a manual on women’s clothing in Northern Europe through the years 1360-1415, and is aimed at reenactors. The time frame - 1360-1415 - means that we are in the beginning of the Late Medieval period as defined by English and northern European historians (normally set to 1300-1500). The geographical setting is Northern Europe, here defined as: “from Germany til (sic) central Sweden, and from the Baltic region to the Norwegian West coast.”